Analysis of the resistance and durability of concrete with photoluminescent pigments - Vargas Chang, Esther Joni (2024)
This study aimed to analyze the impact of photoluminescent pigments on the mechanical properties of concrete, specifically its resistance to compression and bending. The type of research was descriptive with a review of previous experimental works that evaluate concrete with pigments in concentrations of 0%, 1%, 2%, and 4%. The results showed a significant decrease in compressive and flexural strength with increasing pigment concentration, the reduction being up to 31.4% and 16.7%, respectively. Despite these decreases, there will be an improvement in visibility in the dark and an increase in the luminous intensity of the pigmented concrete. However, an increase in water absorption and lower resistance to freeze-thaw cycles was also found, affecting the durability of the material. The study concludes that photoluminescent pigments have a negative impact on the compressive and flexural strength as well as the durability of concrete and suggests that, although photoluminescent pigments provide aesthetic value, their use in structural applications should be carefully evaluated to balance the visual benefits with the structural integrity and durability of concrete.